2007
DOI: 10.1080/02844310600699499
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a large defect of the chest wall in a child using a negative pressure wound dressing

Abstract: Vacuum-assisted closure(VAC) is a simple wound healing tool in plastic surgery. We report a large thoracic defect in a child, in which the VAC was used to cover an exposed polytetrafluoroethylene prosthesis. The VAC saved the prosthesis and induced complete granulation of the wound, which healed completely in five weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…However, the extensive chest wound of our patient was infected and it was difficult to find a vessel to perform vascular anastomosis. In addition, although negative pressure wound therapy and vacuum‐assisted closure techniques represent two alternatives to reconstruct anterior chest wall defect, no reports are available using these methods to treat a full‐thickness chest wall defect with exposure of pericardium and ribs because the negative pressure may be harmful for the respiratory and cardiovascular systems of the patient. Skoracki et al indicated in their study that the use of negative pressure wound therapy was contraindicated over exposed organs, and the manufacturer of vacuum‐assisted closure devices also warned against their use in patients whose wounds contained necrotic tissues .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extensive chest wound of our patient was infected and it was difficult to find a vessel to perform vascular anastomosis. In addition, although negative pressure wound therapy and vacuum‐assisted closure techniques represent two alternatives to reconstruct anterior chest wall defect, no reports are available using these methods to treat a full‐thickness chest wall defect with exposure of pericardium and ribs because the negative pressure may be harmful for the respiratory and cardiovascular systems of the patient. Skoracki et al indicated in their study that the use of negative pressure wound therapy was contraindicated over exposed organs, and the manufacturer of vacuum‐assisted closure devices also warned against their use in patients whose wounds contained necrotic tissues .…”
Section: Discussionmentioning
confidence: 99%
“…The injury following major electrical burn occurs occasionally in the workplace, and the reconstruction of anterior chest wall defect as a result of this injury represents a very challenging surgery, as some life‐threatening complications may arise owing to delayed or failed reconstruction in such scenario. Many techniques are currently available for the repair of anterior chest wall defect, such as split skin graft , flap transplantation , negative pressure wound therapy , and vacuum‐assisted closure . However, these previous methods are considered not suitable to repair anterior chest wall defect following major electrical burn as in this case immediate coverage of the wound is of vital importance.…”
Section: Introductionmentioning
confidence: 99%
“…An der Körperoberfläche wird die Unterdrucktherapie auch zum temporären Bauchdeckenverschluss und bei größeren Substanzdefekten z. B. der Bauch- oder Thoraxwand genutzt [ 3 , 4 ].…”
Section: Hintergrundunclassified
“…ITNPT was given over a duration of m = 10 days (2-18 days), change interval m = 4 d (2-6 d). The application of intrathoracic negative pressure dressings was performed m = 3.5 (1)(2)(3)(4)(5)(6) times. The empyema cavity continuously reduced in size and was cleansed by the suction.…”
Section: Introductionmentioning
confidence: 99%
“…Negative pressure is created by connecting a hose to an electronic pump. On the body surface, negative pressure therapy is also used for temporary abdominal wall closure and for larger tissue defects, e.g., of the abdominal or thoracic wall [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%